Migration and Crime: Does Migration Really Effect on Increasing State Crime? - Jahan, Bushrat (Essays of Faculty of Law University of Pécs, Yearbook of [year], 2025)
Migration has become a global issue for the last few years. Immigrants from the third-world country are tending to get into countries of Western Europe and America. With this increasing number of immigrants, the debate also arises that the higher level of immigration led to a higher level of crime. However, the connection between migration and crime is not so simple to be shown. The immigrant policy of the state for documentation and legalization of immigrant residents also has an impact on establishing the connection between their behavior and the state they have migrated in. This study aims to find out how far migration is responsible for the increasing crime rate. There will be also discussed the behavioral differences between documented and non-documented immigrants in terms of obtaining work and legal wages. Besides, immigrant victimization also will be focused.